MEKANISME PERTAHANAN EGO TOKOH NOVEL DADAISME KARYA DEWI SARTIKA KAJIAN PSIKOLOGI SASTRA - M. Rudi Gunawan Parozak; Fadma Rosita (JURNAL ILMIAH GLOBAL EDUCATION, 2021)
This research discusses anxiety and ego defense mechanisms . The author discusses this novel because first, this novel is very interesting and challenging to read because of the complexity of the relationships between the characters and the anxiety that is so great and the story is so interesting by the author that the writer feels challenged to analyze it. Second, get evidence about anxiety and ego mechanisms performed by the characters. Third, the authors relate the events in the Novel Dada with the phenomena that exist in real life.The objectives of this research are; 1) to describe the forms of anxiety experienced by the characters, 2) to describe the ego defense mechanisms that were carried out by the characters to reduce anxiety. 3) linking the phenomenon of the condition of society to one of the worries experienced by the character. The subject of this research is the novel Dadaisme by Dewi Sartika published by the publisher Mahatari Yogyakarta. The object of this research includes the forms of anxiety, the factors behind the anxiety and ego defense mechanisms to reduce anxiety in the novel Dadaisme by Dewi Sartika. The data collection methods used the description method, the literature review method, and the reading notes method. The research instrument used a data card. The method of data analysis in this study used a qualitative descriptive method. The results of the research that have been done are (1) the forms of anxiety faced by the characters are neurotic anxiety , morality anxiety , and realistic anxiety , (2) the factors that cause anxiety are factors that originate from the characters themselves and from outside. the character's self, which occurs as a result of past and present trauma, (3) the ego defense mechanisms used by the characters to reduce the anxiety they face include repression, regression, fixation, projection ( paranoia ), displacement , and sublimization.